The Use of Mentimeter Application in Teaching and Learning Process to Accommodate Different Learning Styles in an Online ESL Classroom - Noor Alhusna Madzlan; Lim Shu Hui (The English Teacher, 2022)
The sudden outbreak of Covid-19 pandemic in 2019 resulted in the transition from face-to-face classes to online lessons. However, some of the online tools are not suitable to be used in online ESL classrooms due to the inability to accommodate different students’ learning styles. The aim of this research is to study how Mentimeter can fulfil this requirement and the learning theories included. The survey on perception of pre-service ESL teachers after using Mentimeter has been assessed with a questionnaire and it is proven from the results that Mentimeter is able to accommodate different learning styles due to its various features. The study also takes a theoretical approach to analyze the Mentimeter features and the students’ learning styles, hoping that this research can enhance both teachers’ and students’ teaching and learning experience. The study has demonstrated that Mentimeter is an ideal educational tool with the support of pedagogical reasons. Therefore, more support should be provided by MOE to teachers as to ensure assessment for learning is practised widely by English teachers in the nation.